Effects of Water Quality on Dissolution of Yerba Mate Extract Powders. (24th February 2014) - Huang, Wen-Ying; Lee, Pei-Chi; Hsu, Jaw-Cherng; Lin, Yu-Ru; Chen, Hui-Ju; Lin, Yung-Sheng
Abstract : Yerba mate tea is known as one of the most popular nonalcoholic beverages favoured by South Americans due to its nutrition facts and medicinal properties. The processing of yerba mate tea is found to affect the properties of its final forms. This study presents an investigation into the effects of water sources on the dissolution of yerba mate extract powders. Comparisons were conducted between yerba mate teas prepared by dissolving yerba mate extract powders into tap water and deionized water. Topics to be explored in this work are the major compositions and antioxidant activities, including total phenol content, reducing power, DPPH scavenging activity, and ABTS + scavenging capacity. It is indicated that there is little difference for antioxidant activities and major constituents of yerba mate teas between both water sources. However, a deeper color is seen in the tap water case, resulting from the reaction between tannic acid and ions. This research finding can be treated as a way to benefit the yerba mate tea processing for applications.